Effect of hypoxic training on inflammatory and metabolic risk factors: a crossover study in healthy subjects. Issue 1 (13th January 2014) - Shi, Bateer; Watanabe, Tsuneo; Shin, Sohee; Yabumoto, Tamotsu; Takemura, Masao; Matsuoka, Toshio
Abstract The purpose of this study was to investigate the influence of hypoxic physical exercise on metabolic syndrome (MS) risk markers and high‐sensitivity C‐reactive protein (CRP) and to compare its effects on preperitoneal fat, arterial stiffness, and several blood parameters related to MS to those of a control group who trained under normoxic conditions. Fourteen healthy men were examined. Participants performed treadmill exercise 3 days per week for 4 weeks, under either normobaric hypoxic or normobaric normoxic conditions, for 50 min (including a 5‐min warm‐up and 5‐min cool down) after a 30‐min rest period. Exercise was performed at a heart rate (HR) corresponding to 60% of the HR at each individual's maximum oxygen uptake. Training under the different environmental conditions was performed 4 months apart to ensure a sufficient washout period. Waist circumference, preperitoneal fat thickness, brachial‐ankle pulse wave velocity, and high‐sensitivity CRP after training were significantly lower in the hypoxic group than in the normoxic group. Our results suggest that regular short‐term hypoxic training may more effectively reduce arterial stiffness, and thus prevent arteriosclerosis, compared to training performed at a similar exercise intensity under normoxic conditions.